Cert Prep: Unity Certified Associate Game Developer UI and 2D Games. - Thorn, Alan (linkedin.com, 2021)
Prepare for the Unity Certified Associate: Game Developer exam by exploring the fundamentals of creating user interfaces and 2D games in Unity.